2013
DOI: 10.1016/j.molcel.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Control of Protein Quality and Stoichiometries by N-Terminal Acetylation and the N-End Rule Pathway

Abstract: SUMMARY Nα-terminal acetylation of cellular proteins was recently discovered to create specific degradation signals, termed Ac/N-degrons and targeted by the Ac/N-end rule pathway. We show that Hcn1, a subunit of the APC/C ubiquitin ligase, contains an Ac/N-degron that is repressed by Cut9, another APC/C subunit and the ligand of Hcn1. Cog1, a subunit of the Golgi-associated COG complex, is also shown to contain an Ac/N-degron. Cog2 and Cog3, direct ligands of Cog1, can repress this degron. The subunit decoy te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
364
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(388 citation statements)
references
References 40 publications
17
364
1
1
Order By: Relevance
“…A recent proteomic analysis on NatB, an N-terminal acetylase, has reported that the global protein abundance of NatB substrates is not significantly altered in NatB mutants (Gao et al 2016). This apparent dichotomy may be rationalized in several ways, which include sufficient residual acetylation in the mutant, additional unforeseen sequence specificity of the Ac-N-end rule pathway or that many of the N-termini are inaccessible for the Ac-N-end rule pathway as this pathway has been reported to degrade protein subunits that are in excess of their target complex (Shemorry et al 2013). In support of a model where many of these acetylated N-termini may not be directly accessible for the Ac-N-end rule pathway is the recent report that demonstrates this pathway is involved in the degradation of several HSP90 client proteins (Oh et al 2017).…”
Section: Ac-n-end Rulementioning
confidence: 99%
“…A recent proteomic analysis on NatB, an N-terminal acetylase, has reported that the global protein abundance of NatB substrates is not significantly altered in NatB mutants (Gao et al 2016). This apparent dichotomy may be rationalized in several ways, which include sufficient residual acetylation in the mutant, additional unforeseen sequence specificity of the Ac-N-end rule pathway or that many of the N-termini are inaccessible for the Ac-N-end rule pathway as this pathway has been reported to degrade protein subunits that are in excess of their target complex (Shemorry et al 2013). In support of a model where many of these acetylated N-termini may not be directly accessible for the Ac-N-end rule pathway is the recent report that demonstrates this pathway is involved in the degradation of several HSP90 client proteins (Oh et al 2017).…”
Section: Ac-n-end Rulementioning
confidence: 99%
“…Recently Shemorry et al (49) showed that the N-terminally acetylated Cog1 subunit of the multimeric COG complex of S. cerevisiae involved in Golgi transport is a target of the Not4 E3 ligase with subsequent degradation by the proteasome. It could be shown that moderately overexpressed Cog1 could be stabilized by co-expression of interacting subunits of the COG complex.…”
Section: Discussionmentioning
confidence: 99%
“…1B) (17,23,24). The degradation signals and E3 Ub ligases of the Ac/N-end rule pathway are called Ac/N-degrons and Ac/N-recognins, respectively.…”
Section: Significancementioning
confidence: 99%
“…1) (9,11,12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The main determinant of an N-degron is a destabilizing N-terminal residue of a protein.…”
mentioning
confidence: 99%